Dietary Fatty Acids and Predementia Syndromes - Vincenzo Solfrizzi; Vincenza Frisardi; Cristiano Capurso; Alessia D' Introno; Anna M. Colacicco; Gianluigi Vendemiale; Antonio Capurso; Francesco Panza (The Scientific World Journal)
An increasing body of epidemiological evidence suggests that elevated saturated fatty acids (SFA) could have negative effects on age-related cognitive decline (ARCD). Furthermore, a reduction of risk for cognitive decline and mild cognitive impairment (MCI) has been found in population samples with elevated fish consumption, and high intake of monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA), particularly n-3 PUFA. However, recent findings from clinical trials with n-3 PUFA supplementation showed efficacy on depressive symptoms in non–Vapolipoprotein E (APOE) ε4 carriers, and on cognitive symptoms only in very mild Alzheimer's disease (AD) subgroups, MCI patients, and cognitively unimpaired non-APOE ε4 carriers. These data, together with epidemiological evidence, support the idea that n-3 PUFA may play a role in maintaining adequate cognitive functioning in predementia syndromes, but not when the AD process has already taken over. Therefore, at present, no definitive dietary recommendations on fish and unsaturated fatty acids consumption, or lower intake of saturated fat, in relation to the risk for dementia and cognitive decline are possible.